2021
DOI: 10.3390/cancers13092066
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis, Inhibition of MCL-1, and VEGF-A Expression Are Associated with the Anti-Cancer Efficacy of Magnolol Combined with Regorafenib in Hepatocellular Carcinoma

Abstract: While regorafenib was approved for the treatment of advanced HCC in 2017, with a partial response and survival benefit; other combination agents to facilitate the efficacy of regorafenib still need to be explored. Magnolol is a potential natural anti-tumor compound for many types of cancers. Combination indexes calculated on the basis of both in vitro and in vivo models have indicated a synergistic effect of the combination of regorafenib and magnolol. The overexpression of the VEGF-A protein significantly dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…In the present study, co-amorphous curcumin-magnolol was designed based on their solubility/dissolution defects and potential drug combination advantages. Curcumin (CUR, Figure 1 a) and magnolol (MAG, Figure 1 b) have gained increasing interest because of their multiple biological activities (such as antioxidant, anticancer, antimicrobial, and anti-inflammatory) [ 19 , 20 , 21 , 22 , 23 ]. Moreover, the two drugs have generated combined therapeutic effects in cardiovascular diseases, Alzheimer’s disease, and neurodegenerative diseases [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, co-amorphous curcumin-magnolol was designed based on their solubility/dissolution defects and potential drug combination advantages. Curcumin (CUR, Figure 1 a) and magnolol (MAG, Figure 1 b) have gained increasing interest because of their multiple biological activities (such as antioxidant, anticancer, antimicrobial, and anti-inflammatory) [ 19 , 20 , 21 , 22 , 23 ]. Moreover, the two drugs have generated combined therapeutic effects in cardiovascular diseases, Alzheimer’s disease, and neurodegenerative diseases [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latest research found that the JAK2/STAT3 pathway participates in the process of AngⅡ-induced myocardial remodeling by promoting myocardial hypertrophy and fibrosis (Ye et al, 2020). In this study, we found that the phosphorylation levels of JAK2 and STAT3 were evidently Magnolol is one of the foremost effective ingredients of traditional Chinese medicine Magnolia Officinalis, which has received widespread attention due to its anti-inflammatory (Zhou et al, 2019) and anti-tumor (Chen et al, 2021a) effects. A recent study reported that magnolol could ameliorate the vascular remodeling in monocrotaline-induced PAH rats (Chang et al, 2018).…”
Section: Discussionmentioning
confidence: 59%
“…Magnolol is one of the foremost effective ingredients of traditional Chinese medicine Magnolia Officinalis , which has received widespread attention due to its anti-inflammatory ( Zhou et al, 2019 ) and anti-tumor ( Chen et al, 2021a ) effects. A recent study reported that magnolol could ameliorate the vascular remodeling in monocrotaline-induced PAH rats ( Chang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of anti‐apoptotic proteins and induction of apoptosis by complementary agents have been presented to boost the anti‐HCC efficacy of therapeutic agents. 38 , 39 In addition to the reduction of anti‐apoptotic proteins, expression of apoptotic proteins cleaved‐caspase‐3, −8, −9, and Endo‐G was significantly increased by quetiapine treatment (Figure 3 A‐C). Endo‐G is a caspase‐independent death effector to trigger nucleosome DNA fragmentation leading to tumor cell death.…”
Section: Discussionmentioning
confidence: 96%